Silibinin In Vitro Protects A549 Cells from Staphylococcus aureus-Mediated Injury and In Vivo Alleviates the Lung Injury of Staphylococcal Pneumonia - Wang, Xin; Dong, Jing; Dai, Xiaohan; Zhang, Yu; Wang, Jianfeng; Li, Hongen; Lu, Chongjian; Tan, Wei; Gao, Xiaohan; Deng, Xuming; Bu, Shijin; Niu, Xiaodi (Planta Medica, 2013)
In this study, hemolysis, Western blot, and real-time RT-PCR assays were performed to evaluate silibininʼs activity against S. aureus α-toxin secretion. In addition, live/dead cell staining and lactate dehydrogenase activity assays were introduced to examine the influence of silibinin on α-toxin-induced cell injury in human alveolar epithelial cells. Furthermore, we tested the influence of silibinin on S. aureus pneumonia in a mouse model. We show that silibinin inhibits the expression of α-toxin in a dose-dependent manner and alleviates α-toxin-induced lung cell injury. The IC50 of silibinin that inhibits the hemolytic activity of S. aureus was 14.33 µg/mL for strain 8325–4. Moreover, this compound provides effective protection on the lung injury of staphylococcal pneumonia.
Keywords: Staphylococcus aureus; α-toxin; silibinin; Silybum marianum; Asteraceae; A549 cells; pneumonia